1997
DOI: 10.1071/a96003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil drought during the generative development phase on seed yield and nutrient uptake of faba bean (Vicia faba)

Abstract: The effects of periods of drought during different phases of reproductive growth of faba bean (Vicia faba L.) cv. Xichang Dabai were investigated in a pot experiment at Xichang Agricultural College, China. Parameters were total dry matter; seed yield; yield components; concentrations of nitrogen, phosphorus, and potassium; and total uptake in different organs. All drought treatments decreased total dry matter production and seed yield per plant. Plants subjected to drought from initiation of pod-set to full po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
1
13
0
3
Order By: Relevance
“…It is still necessary to identify information gaps in the research and suggest future needs. According to Xia (1997), N, P, and K uptake decreased significantly under water stress in faba bean. In a study carried out with chickpea, 11 screened cultivars varied greatly with respect to nutrient uptake in both optimal and drought conditions (Gunes et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…It is still necessary to identify information gaps in the research and suggest future needs. According to Xia (1997), N, P, and K uptake decreased significantly under water stress in faba bean. In a study carried out with chickpea, 11 screened cultivars varied greatly with respect to nutrient uptake in both optimal and drought conditions (Gunes et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…In general, the number of pods per plant seems to be the yield component that is most affected by drought stress during flowering and can reduce final grain yield up to 70% depending on the dura-tion and intensity of the stress period (Lopez et al, 1996). On the other hand, the number of seeds per pod of dry beans seems to be a more consistent yield component under drought stress and seed size variation has been reported to be of minor importance (Xia, 1997;Farah, 1981). However, less is known about the impact of drought stress on the distribution of flowers and pods of different nodes and plant axes.…”
Section: Introductionmentioning
confidence: 99%
“…Soil water deficits that occur during the reproductive growth are considered to have the most adverse effect on crop yield (Costa-Franca et al, 2000;Baigorri et al, 1999). Several studies have shown that water deficits imposed during the reproductive development of dry beans can decrease the number of flowers, pods and number of seeds per pod (Xia, 1997;Loss & Siddique, 1997). The total number of flowers in some varieties may be reduced up to 47% under drought conditions affecting the number of pods per plant.…”
Section: Introductionmentioning
confidence: 99%
“…El estrés hídrico tiene su efecto más adverso durante la fase reproductiva (Costa et al, 2000). Diversos estudios muestran que se reduce el número de flores, vainas y semillas por vaina (Xia, 1997), en algunas variedades de frijol la sequía disminuye hasta 47% el número de flores, afectando el número de vainas por planta (Nuñez et al, 2005). También se ha observado que el aborto de vainas bajo condiciones de estrés hídrico puede variar de 21 a 65% (Mwanamwenge et al, 1999).…”
Section: Introductionunclassified